pCyP B: a chloroplast-localized, heat shock-responsive cyclophilin from fava bean. - Luan, S (1994)
When the immunosuppressants cyclosporin A (CsA) and FK506 bind to their intracellular receptors (immunophillins), they form complexes that bind to calcineurin and block calcineurin-dependent signaling pathways in immune cells. Previously, we reported that higher plants also express immunophilins and have a Ca(2+)-dependent signaling pathway sensitive to immunophilin-ligand complexes. Based on an N-terminal peptide sequence of a chloroplast-localized cyclophilin (pCyP B), we isolated a cDNA clone encoding the preprotein of the cyclophilin. The deduced amino acid sequence of this cDNA starts with a putative transit sequence for chloroplast targeting. The mature pCyP B protein has rotamase activity with low-substrate specificity. Enzyme activity was inhibited by CsA with an inhibition constant of 3.9 nM. Similar to other CyPs from mammalian cells, pCyP B, when complexed with CsA, inhibited the phosphatase activity of bovine calcineurin. The mRNA level of pCyP B was high in leaf tissue but was not detectable in roots. Expression of the transcript in the leaf tissues was regulated by light and induced by heat shock. These findings illustrate the conserved nature of cyclophilin proteins among all of the eukaryotes and suggest that cyclophilins have a unique mode of regulation in higher plants.